Is there a correlation between maternal serum TGF-β1 levels and fetal hydronephrosis?. (2nd April 2016) - Seven, Ali; Savran, Bircan; Koçak, Emel; Tok, Sermin; Yüksel, Kadriye Beril; Gözükara, İlay and Kabil Kucur, Suna
Abstract: Objective : We aimed to identify a noninvasive marker for clinically significant fetal uropathies. To achieve this aim, we detected TGF (transforming growth factor)-β1 serum level which rises in neonatal hydronephrosis, in pregnant patients with fetal hydronephrosis. Materials and methods : We evaluated 44 patients, all of whom were pregnant and had a gestational age between 20 and 30 weeks. Twenty-two patients had normal maternal renal ultrasound imaging and had a fetus with fetal hydronephrosis (Group A). The remaining twenty-two patients had normal maternal and fetal renal ultrasound imaging (Group B). The maternal serum levels of TGF-β1 were measured with a sandwich enzyme-linked immunosorbent assay (ELISA) using a commercially available kit. Results : The median value for the study group was 55.90 pg/mL (9.67 ± 574.45) and for the control group was 59.49 pg/mL (12.49 ± 402.04). There was no statistical difference in serum TGF-β1 levels between the groups ( p = 0.769 – Mann–Whitney U test). In the study group, the diameter of the right renal pelvis was 5.7 mm (5.1–8.9 mm), while the diameter of left renal pelvis was 5.75 mm (5.3–10.04 mm). Conclusion : In our study, the circulating TGF-β1 levels were not statistically different in the fetal hydronephrosis group when compared to the controls. According to our study, TGF-β1 is not useful in the detection and follow-up of fetal hydronephrosis. We therefore require further studies involving larger groups with moderate or severe fetal hydronephrosis to detect the usefulness of the serum levels of TGF-β1 in pregnant women with fetal hydronephrosis.